Three-dimensional printing for complex orthopedic cases and trauma: A blessing - Raju Vaishya; Vipul Vijay; Abhishek Vaish; Amit Kumar Agarwal (Apollo Medicine, 2018)
Three-dimensional (3D) printing technology is penetrating the health-care field at an astonishing rate. In the clinical settings, 3D printing, as a novel additive manufacturing technique, is mainly applied in orthopedics. A group of 3D printing-based patient-specific osteotomy instruments, orthopedic implants, and dental implants have been available for clinical use. The uses of 3D printing have been explored in the field of arthroplasty, sports medicine, spine, pediatric orthopedics, and trauma. The 3D printing technology may provide a chance for the Indian orthopedists and technicians to independently develop innovative medical devices to catch up with their Western counterparts. Its role in patient as well as medical education is also worth exploring. With these myriad applications, 3D printing holds great promise to improve patient as well as surgeon satisfaction in the near future. We discuss the process, applications, and advantages of 3D printing in this review article.